2022
DOI: 10.1097/icu.0000000000000853
|View full text |Cite
|
Sign up to set email alerts
|

Cell therapy in corneal endothelial disease

Abstract: Purpose of reviewEndothelial keratoplasty is the current gold standard for treating corneal endothelial diseases, achieving excellent visual outcomes and rapid rehabilitation. There are, however, severe limitations to donor tissue supply and uneven access to surgical teams and facilities across the globe. Cell therapy is an exciting approach that has shown promising early results. Herein, we review the latest developments in cell therapy for corneal endothelial disease.Recent findingsWe highlight the work of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…AS-OCT is an invaluable aid in these situations and may reduce the rates of primary or immediate post-operative graft failure. Cell therapy for corneal endothelial disease is an emerging area of research that has the potential to revolutionize the field [ 44 ]. In this study, we reported for the first time the novel application of AS-OCT to attempt to predict a successful cell injection in a model of bullous keratopathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AS-OCT is an invaluable aid in these situations and may reduce the rates of primary or immediate post-operative graft failure. Cell therapy for corneal endothelial disease is an emerging area of research that has the potential to revolutionize the field [ 44 ]. In this study, we reported for the first time the novel application of AS-OCT to attempt to predict a successful cell injection in a model of bullous keratopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative solutions that overcome the constraints of donor shortage are required, and numerous options are being investigated. These include regenerative medicine approaches, such as Descemet Stripping Only (DSO) [ 48 ], synthetic approaches such as the EndoArt (EyeYon Medical, Ness Ziona, Israel), an artificial endothelial layer [ 49 ], and a plethora of bioengineering approaches that have been comprehensively reviewed elsewhere [ 44 , 50 , 51 , 52 ]. CECI is one such promising solution in a growing field, but questions remain regarding its long-term efficacy and safety.…”
Section: Discussionmentioning
confidence: 99%
“…Cell therapy has emerged as a promising avenue for addressing corneal endothelial dysfunction, offering potential solutions to the limitations associated with traditional treatments such as corneal transplantation. Recent research has shed light on the utilization of various cell types, including human embryonic stem cells, human induced pluripotent stem cells, cadaveric human corneal endothelial cells, and corneal endothelial progenitors, to generate populations of corneal endothelial cells for intracameral injection [ 24 ]. These studies have yielded successful functional outcomes in animal models, underscoring cell therapy’s promising role in treating corneal endothelial diseases.…”
Section: Reviewmentioning
confidence: 99%
“…More clinical data is needed to determine the role of endothelial cell therapy as well as possible variations in adjunct therapeutics-pharmacological and/or surgical-in Fuchs endothelial corneal dystrophy patients. www.co-ophthalmology.com gelatin, hydrogel, chitosan, agarose, and poly-elysine, as well as decellularized tissue such as human DM, corneal stroma, lens capsule, and posterior lamellae of the porcine or bovine cornea [31][32][33][34][35][36]. The techniques for implantation in animal models have been shown to be greatly similar to that of endothelial keratoplasty [33,37].…”
Section: Key Pointsmentioning
confidence: 99%
“…Transplantation of cultivated HCEC on carriers has been proposed as a mean to deliver HCEC to the recipient; proponents of this technique theorize that it may be favorable to maintain the polarity of transplanted endothelial cells [31–33]. Several biomaterials have been tested as HCECs carriers, and these include collagen, amniotic membrane, human platelet lysate and fibrin, silk fibroin, gelatin, hydrogel, chitosan, agarose, and poly-e-lysine, as well as decellularized tissue such as human DM, corneal stroma, lens capsule, and posterior lamellae of the porcine or bovine cornea [31–36]. The techniques for implantation in animal models have been shown to be greatly similar to that of endothelial keratoplasty [33,37].…”
Section: Introductionmentioning
confidence: 99%